Chapter Tourism and territorial economy: beyond satellite accounting - ANTOLINI, Fabrizio (Proceedings e report, 2023)
The tourism sector can be an important factor for the economic development. The increase in the present population, due to tourist flows, also activates a series of other sectors, generating significant economic benefits. At international level, the main tool for this type of evaluation has been identified in satellite accounting, which estimates the value added of the tourism sector, possibly increased by that coming from other similar sectors, obtaining the tourism value added. At European level, satellite accounting is a voluntary exercise for countries, which almost never finds a dimension of territorial detail, limiting itself to the national level. Having an accounting representation at a territorial level, even if only regional, would instead be very useful for both descriptive and forecasting purposes (Input-Output). In order to reproduce the estimates of satellite accounting at a territorial level, it is important to have monetary (tourist expenses) and non-monetary (attendance) variables. For Italy, if counted from the offer side rather than the demand side, these variables are available with at least regional territorial detail. On the other hand, the temporal alignment of this information is different, since tourist spending and tourist presences come from different surveys. However, we could start developing a methodology that starts from the offer, using value added as an accounting approach. The advantages would be important: the statistical information used would in fact be that contained in the Business Register FRAME, with considerable advantages from the point of view of the timeliness and homogeneity of the statistical data. Naturally, the various economic activities must be weighed for their link with tourism sector. This source of information could enjoy also the possibility of having information deriving from electronic invoicing. In this work, an attempt to estimate the tourism value added through the offer side is experimented at the regional level.